Not all ECB meetings are created equal - Sinem Kandemir; Peter Tillmann (Philipps-University Marburg, School of Business and Economics, 2023)
Most meetings of the Governing Council of the ECB take place intra muros at the ECB's premises in Frankfurt. Some meetings, however, are held extra muros, i.e. outside Frankfurt, hosted by one of the national central banks. This paper uses high-frequency surprises from meeting days to show that the standard deviation of surprises is higher when the ECB meets intra muros. This difference is mostly due to larger timing, forward guidance and QE surprises when meeting in Frankfurt. We show that the transmission of policy surprises to longer-term interest rates is significantly weaker when meeting extra muros. In addition, when the meeting takes place extra muros, the wording of the ECB communication during the press conference is significantly more similar to the preceding meeting. The results suggest that the important decisions are taken in Frankfurt and that the ECB avoids large changes to the policy path when meeting extra muros. The difference across meeting types has consequences for the macroeconomic impact of monetary policy.
Keywords: E58; E43; 330; monetary policy; expectations; central bank communication; monetary policy committee; text analysis